Rapid and selective extraction of trace amount of Pb(II) in aqueous samples using a magnetic ion-imprinted polymer and detection by flame atomic absorption spectrometry - Babaee, Saeed; Hosseini, Seyed Ghorban; Mirzaei, Mohammad (Eclética Química, 2019)
A magnetic Pb(II) ion-imprinted polymer was synthesized using magnetic Fe3O4@SiO2 nanospheres as supporter, n-benzoyl-n-phenyl hydroxylamine as ligand, 4-vinyl pyridine as monomer, ethylene glycol dimethacrylate as crosslinker and 2,2′-azobis(isobutyronitrile) as the initiator. The template was removed from the polymer using 4 mL of HCl (2 mol L-1). The chemical structure, morphology-particle size, elemental analysis, thermal behavior and magnetic properties of the sorbent were evaluated using Fourier-transform infrared spectroscopy, scanning electron microscopy & ImageJ software - Energy dispersive X-ray system, thermal gravimetric analysis and vibrating sample magnetometry. Various parameters such as pH, equilibrium extraction time, temperature and the eluent were optimized. The results showed the sorbent adsorption capacity was 92.3 mg g-1 in pH 6.0 media, equilibrium time of 7 min at 40 °C. Calibration linearity was 2-150 µg L-1 with detection limit of 0.3 µg L-1. The prepared sorbent had high selectivity and was successfully applied to the removing of lead in real samples.